N-acetylcysteine alleviates angiotensin II-mediated renal fibrosis in mouse obstructed kidneys - Shen, Yang; Miao, Nai-jun; Xu, Jin-lan; Gan, Xin-xin; Xu, Dan; Zhou, Li; Xue, Hong; Zhang, Wei; Lu, Li-min (Acta pharmacologica Sinica, 2016)
Aim： To investigate the effects of ROS scavenger N-acetylcysteine （NAC） on angiotensin II （Ang II）-mediated renal fibrosis in vivo and in vitro. Methods： Mice were subjected to unilateral ureteral obstruction （UUO）, and then treated with vehicle or NAC （250 mg/kg, ip） for 7 days. Histological changes of the obstructed kidneys were observed with Masson＇s trichrome staining. ROS levels were detected with DHE staining. The expression of relevant proteins in the obstructed kidneys was assessed using Western blotting assays. Cultured rat renal fibroblast NRK-49F cells were used for in vitro experiments. Results： In the obstructed kidneys, Ang II levels were significantly elevated, and collagen I was accumulated in the interstitial spaces. Furthermore, ROS production and the expression of p47 （a key subunit of NADPH oxidase complexes） were increased in a time- dependent manner; the expression of fibronectin, α-SMA and TGF-β were upregulated. Administration of NAC significantly alleviated the fibrotic responses in the obstructed kidneys. In cultured NRK-49F cells, treatment with Ang II （0.001-10 pmol/L） increased the expression of fibronectin, collagen I, α-SMA and TGF-β in dose-dependent and time-dependent manners. Ang II also increased ROS production and the phosphorylation of Smad3. Pretreatment with NAC （5 pmol/L） blocked Ang II-induced oxidative stress and ECM production in the cells. Conclusion＂ In mouse obstructed kidneys, the fibrotic responses result from Ang II upregulation can be alleviated by the ROS scavenger N-acetylcysteine.